(untitled) (Edad Media. Revista de Historia, 2024)
This study focuses on the historical landscape of the Douro River. The regional and local values of medieval cultural heritage elements were explored from “Demarcações de Fronteira” - a demarcation book dated from 1537-1538 - to understand the places and medieval testimonies of political, social, and economic relations between the two medieval kingdoms of Portugal and Castile. A document analysis is intended to identify and describe the cultural elements of a specific place and a particular time and discern resilient cultural features in the landscape. In parallel, a cartographic analysis could help to identify, characterize, and localize the late medieval landscape (beginning of the 16th century). This analysis is fundamental for comparing other periods and studying the landscape resilience.